Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/cells12182255
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin System Is a Pharmacological Target to Counteract Pain and Its Comorbid Mood Alterations in an Osteoarthritis Murine Model

Giulia Galimberti,
Giada Amodeo,
Giulia Magni
et al.

Abstract: Osteoarthritis (OA) is the most prevalent joint disease associated with chronic pain. OA pain is often accompanied by mood disorders. We addressed the role of the Prokineticin (PK) system in pain and mood alterations in a mice OA model induced with monosodium iodoacetate (MIA). The effect of a PK antagonist (PC1) was compared to that of diclofenac. C57BL/6J male mice injected with MIA in the knee joint were characterized by allodynia, motor deficits, and fatigue. Twenty-eight days after MIA, in the knee joint,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Subsequent studies supported the PKS's physiological role in nociception, as PKR and PK2 KO mice were less sensitive to noxious stimuli than wildtype (WT) mice, with less hyperalgesia onset after tissue damage [87][88][89][90]. A role of the PKS has also been demonstrated in the development and maintenance of both chronic inflammatory [91,92] and neuropathic pain of various etiologies [93][94][95][96][97][98][99][100][101]. In these studies, it has been well demonstrated that the presence of aberrant pain was associated with an upregulation in PK2 and PKRs, and that selective PKS antagonism was able to counteract pain symptoms and neuroinflammation.…”
Section: Evidence Of the Pks In Pain: Focus On Ibd Modelmentioning
confidence: 94%
“…Subsequent studies supported the PKS's physiological role in nociception, as PKR and PK2 KO mice were less sensitive to noxious stimuli than wildtype (WT) mice, with less hyperalgesia onset after tissue damage [87][88][89][90]. A role of the PKS has also been demonstrated in the development and maintenance of both chronic inflammatory [91,92] and neuropathic pain of various etiologies [93][94][95][96][97][98][99][100][101]. In these studies, it has been well demonstrated that the presence of aberrant pain was associated with an upregulation in PK2 and PKRs, and that selective PKS antagonism was able to counteract pain symptoms and neuroinflammation.…”
Section: Evidence Of the Pks In Pain: Focus On Ibd Modelmentioning
confidence: 94%